Enhancing of Corrosion Protection of Steel Rebar in Concrete Using TiO2 Nanoparticles as Additive - Khudhair, Noor Ali; Al-Sammarraie, Abdulkareem Mohammed Ali (Iraqi Journal of Science, 2019)
Nanomaterials became targeted materials for many important applications due to its huge surface area and quantum confinement effects. In this work TiO2 nanoparticles (30nm) were used as additive to enhance the corrosion protection of steel rebar in artificial concrete solution (Ca(OH)2 (2g), KOH (22.44mg), NaOH (8mg) in 1L of distilled water) against saline environment (3.5%NaCl) at four temperatures; 20, 30, 40, and 50á´¼C. Three different concentrations of TiO2 NPs were used namely; 1, 3, and 5% by weight. The corrosion parameters and pitting probability were followed using Tafel and cyclic polarization plots respectively. Protection enhancement was recorded at all TiO2 percent used and efficiencies of 75-86% were achieved. Using TiO2 NPs reduces but not diminished the pitting hysterias loop area. The results supported by surface morphology examination using atomic force microscope (AFM).